Isolation and Characterization of Multipotent Turkey Tendon-Derived Stem Cells - Qian Liu; Yaxi Zhu; Peter C. Amadio; Steven L. Moran; Anne Gingery; Chunfeng Zhao (Stem Cells International)
Tendon injuries are among the most common and severe hand injuries with a high demand for functional recovery. Stem cells have been identified and isolated from different species and a variety of tissues for the sake of regenerative medicine. Recently, turkey has been suggested as a potential new large animal model for flexor tendon-related research. However, turkey tissue-specific stem cells have not been investigated. Here, we presented the isolation and verification of tendon-derived stem cells (TDSCs) from 6- to 8-month-old heritage-breed turkey. TDSCs were isolated from turkey flexor tendon by plating nucleated cells at the determined optimal density. Approximately 4% of the nucleated cells demonstrated clonogenicity, high proliferation rate, and trilineage differentiation potential after induction culturing. These cells expressed surface antigens CD90, CD105, and CD44, but did not express CD45. There was a high level of gene expression of tenogenic markers in TDSCs, including mohawk, collagen type I, tenascin C, and elastin. Turkey TDSCs also expressed transcription factors PouV, Nanog, and Sox2, which are critically involved in the regulation of stemness. The successful isolation of tendon-derived stem cells from turkey was beneficial for future studies in tendon tissue engineering and would help in the development of new treatment for tendon diseases using this novel animal model.